Arthibition: Designing Augmented Reality for Art Exhibition - Kusuma Dewangga; Kathryn Widhiyanti; Putri Nastiti; Yustus Eko Oktian (Institut Seni Indonesia Yogyakarta, 2023)
ABSTRACTThe Covid-19 pandemic, which occurred in the past 3 years, has forced art activists to reduce activities that involve many people. Meanwhile, art activities that gather many people are still needed as a means of publishing artworks from art activists. Augmented Reality (AR) technology has been widely applied to art exhibitions. To be able to take advantage of this technology, users must come to the exhibition site and scan an object at the exhibition site, resulting in a buildup of visitors at the exhibition site. For this reason, it is necessary to build an application that can be used to enjoy content from the exhibition without having to go to the exhibition location. This study aims to design an application that can be used by the audience to be able to enjoy the content of the art exhibition without having to go to the exhibition site. The use of AR Technology is applied as a tool to ostensibly bring artwork to the location of the application user, so that it can be enjoyed directly. The design of the ARt Exhibition application is expected to be a solution for art activists and connoisseurs to be able to enjoy art exhibitions anywhere personally so that the spread of the Covid-19 virus can be minimized. ARthibition: Mendesain Pameran Seni Rupa dengan Augmented Reality. Pandemi Covid-19 yang terjadi dalam tiga tahun terakhir memaksa para pegiat seni mengurangi aktivitas yang melibatkan banyak orang. Sementara itu, kegiatan seni yang menghimpun banyak orang masih dibutuhkan sebagai sarana penerbitan karya seni dari para pegiat seni. Teknologi Augmented Reality (AR) telah banyak diterapkan dalam pameran seni rupa. Untuk dapat memanfaatkan teknologi ini, pengguna harus datang ke lokasi pameran dan memindai objek di lokasi pameran sehingga terjadi penumpukan pengunjung di lokasi pameran. Untuk itu, perlu dibangun sebuah aplikasi yang dapat digunakan untuk menikmati konten dari pameran tanpa harus pergi ke lokasi pameran. Penelitian ini bertujuan untuk merancang sebuah aplikasi yang dapat digunakan oleh penonton untuk dapat menikmati isi dari pameran seni rupa tanpa harus mendatangi lokasi pameran. Penggunaan teknologi AR diterapkan sebagai alat untuk membawa karya seni ke lokasi pengguna aplikasi sehingga dapat dinikmati secara langsung. Perancangan aplikasi pameran seni rupa ini diharapkan dapat menjadi solusi bagi para pegiat dan penikmat seni rupa untuk dapat menikmati pameran seni rupa dimanapun secara personal sehingga penyebaran virus Covid-19 dapat diminimalkan